2018
DOI: 10.1136/bmj.k4583
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of a low carbohydrate diet on energy expenditure during weight loss maintenance: randomized trial

Abstract: ObjectiveTo determine the effects of diets varying in carbohydrate to fat ratio on total energy expenditure.DesignRandomized trial.SettingMulticenter collaboration at US two sites, August 2014 to May 2017.Participants164 adults aged 18-65 years with a body mass index of 25 or more.InterventionsAfter 12% (within 2%) weight loss on a run-in diet, participants were randomly assigned to one of three test diets according to carbohydrate content (high, 60%, n=54; moderate, 40%, n=53; or low, 20%, n=57) for 20 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
197
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(230 citation statements)
references
References 89 publications
14
197
1
1
Order By: Relevance
“…66 Plausible explanations include the reduction in appetite consistently demonstrated with low-CHO diets that promotes a lower caloric intake in the absence of a specific prescription, 67,68 and the "metabolic advantage" of low-CHO diets that has been shown to significantly increase total energy expenditure to further facilitate weight loss. 69 Furthermore, the present findings suggest that the recommenda- Most vegetables have a low digestible CHO content owing to their high proportions of water and fibre, and often displace the intake of highly processed CHO and discretionary foods. 71,72 Many of the included low-CHO protocols are ultimately in alignment with public health recommendations to consume a vegetable-rich diet for chronic disease prevention and management.…”
Section: Ad Libitum Energy Prescriptions Included Those In Which Partmentioning
confidence: 60%
See 1 more Smart Citation
“…66 Plausible explanations include the reduction in appetite consistently demonstrated with low-CHO diets that promotes a lower caloric intake in the absence of a specific prescription, 67,68 and the "metabolic advantage" of low-CHO diets that has been shown to significantly increase total energy expenditure to further facilitate weight loss. 69 Furthermore, the present findings suggest that the recommenda- Most vegetables have a low digestible CHO content owing to their high proportions of water and fibre, and often displace the intake of highly processed CHO and discretionary foods. 71,72 Many of the included low-CHO protocols are ultimately in alignment with public health recommendations to consume a vegetable-rich diet for chronic disease prevention and management.…”
Section: Ad Libitum Energy Prescriptions Included Those In Which Partmentioning
confidence: 60%
“…Although renal outcomes were not included in the present study, a recent systematic review showed no significant difference with regard to several measures of renal function between high‐protein low‐CHO diets and lower‐protein high‐CHO diets . Plausible explanations include the reduction in appetite consistently demonstrated with low‐CHO diets that promotes a lower caloric intake in the absence of a specific prescription, and the “metabolic advantage” of low‐CHO diets that has been shown to significantly increase total energy expenditure to further facilitate weight loss …”
Section: Discussionmentioning
confidence: 79%
“…However, it is the other component in the dietary energy equation, the impact on energy expenditure, in which potential differences might afford a unique metabolic benefit to eucaloric or modestly hypocaloric ketogenic regimens. There is evidence that there are modest increases in total daily energy expenditure with lower carbohydrate intakes of lower glycemic index but still not sufficiently low as to be true ketogenic diets . Studies performed with diets that differ in glycemic index and glycemic load but still containing substantial carbohydrate, eliminating the possibility of significant ketonemia, suggest small but important increases in postprandial energy expenditure of about 42 kcal/d that are further increased substantially to 278 kcal/d when carbohydrate intake is decreased from 60% to 20% of energy intake .…”
mentioning
confidence: 99%
“…There is evidence that there are modest increases in total daily energy expenditure with lower carbohydrate intakes of lower glycemic index but still not sufficiently low as to be true ketogenic diets . Studies performed with diets that differ in glycemic index and glycemic load but still containing substantial carbohydrate, eliminating the possibility of significant ketonemia, suggest small but important increases in postprandial energy expenditure of about 42 kcal/d that are further increased substantially to 278 kcal/d when carbohydrate intake is decreased from 60% to 20% of energy intake . Although this increase could be in part due to effects on physical activity or the efficiency of energy metabolism in muscle as well, the demonstrated impact on postprandial energy metabolism or diet‐induced thermogenesis strongly indicates that there must be an important impact on general metabolic processes as well.…”
mentioning
confidence: 99%
“…is one of the highest oil-yield crops in the world; however, palm oil is the largest variety of plant oil produced, consumed (30%), and internationally traded in the world, rich in linoleic acid (10%) that is associated with egFAD12 gene [190]. 50~55% carbohydrate diets (especially whole-grain breads, vegetables, and nuts) had minimal risk of mortality [191]. Fruits, vegetables, and whole grains were indispensable among four top diets (Mediterranean diet with five best ranked first, DASH diet with lower blood pressure, Flexitarian diet with lose weight and MIND diet with brain health).…”
Section: Formation Mechanism Of Depending Functionalmentioning
confidence: 99%